An optimized method for tissue glycogen quantification. Issue 4 (18th February 2022) - Schaubroeck, Kyle J.; Leitner, Brooks P.; Perry, Rachel J.
Abstract: Mobilization of glycogen, the short‐term storage form of glucose, is the body's first defense against hypoglycemia and is critical for energy provision during high intensity exercise. Therefore, to advance metabolic research, it is critical to be able to accurately measure glycogen concentrations, including during a prolonged fast and other glycogen‐modulating interventions. Unfortunately, prior enzymatic methods of glycogen detection have been plagued by poor detection in the lower range, high sample mass requirements, and complicated and/or expensive protocols which introduce substantial technical variability into the measured glycogen concentrations. To address these limitations, here we report a streamlined and versatile glycogen extraction protocol coupled with an optimized phenol‐sulfuric acid quantification protocol. With this method, we demonstrate how glycogen can be extracted from only 20 mg of tissue with one centrifugation step and quantified with a highly precise (Intra‐assay %CV ranges from 5–10%) and sensitive (proportionality constant for glycogen = 0.07279 A.U./µg) assay. The cost of all materials equates to 10 cents per sample. Therefore, this method represents an attractive means of assessing ex vivo tissue glycogen content including at the extremes of glycogen concentrations. Abstract : It is critical to be able to accurately measure glycogen concentrations, including during a prolonged fast and other glycogen‐modulating interventions. Unfortunately, prior enzymatic methods of glycogen detection have been plagued by poor detection in the lower range, high sample mass requirements, and complicated and/or expensive protocols which introduce substantial technical variability into the measured glycogen concentrations. To address these limitations, here we report a streamlined and versatile glycogen extraction protocol coupled with an optimized phenol‐sulfuric acid quantification protocol.